2016
DOI: 10.1016/j.jacc.2016.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes of Subcutaneous Versus Transvenous Implantable Defibrillator Therapy

Abstract: The complication rate in patients implanted with an S-ICD or TV-ICD was similar, but their nature differed. The S-ICD reduced lead-related complications significantly, at the cost of nonlead-related complications. Rates of appropriate and inappropriate shocks were similar between the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
156
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(172 citation statements)
references
References 26 publications
12
156
0
4
Order By: Relevance
“…The rate of lead complications is lower in subcutaneous ICDs, but non-lead-related complication are more common. Infections, erosions, defibrillation failure and inappropriate shocks have been reported to occur more frequently in subcutaneous ICDs [76]. A recent metanalysis confirmed these data [77], with the exception of inappropriate shocks due to T wave oversensing which were observed more frequently in patients with a subcutaneous ICD as compared to transvenous ICDs [77].…”
Section: The Future Of Electrical Therapies In Laminopathiesmentioning
confidence: 89%
See 1 more Smart Citation
“…The rate of lead complications is lower in subcutaneous ICDs, but non-lead-related complication are more common. Infections, erosions, defibrillation failure and inappropriate shocks have been reported to occur more frequently in subcutaneous ICDs [76]. A recent metanalysis confirmed these data [77], with the exception of inappropriate shocks due to T wave oversensing which were observed more frequently in patients with a subcutaneous ICD as compared to transvenous ICDs [77].…”
Section: The Future Of Electrical Therapies In Laminopathiesmentioning
confidence: 89%
“…Data show that there are no differences in overall complications between subcutaneous and transvenous ICD but the complications of subcutaneous ICDs can be resolved easier [76]. The rate of lead complications is lower in subcutaneous ICDs, but non-lead-related complication are more common.…”
Section: The Future Of Electrical Therapies In Laminopathiesmentioning
confidence: 99%
“…77 The authors' analysis demonstrated that the S-ICD system was more likely to deliver inappropriate therapy due to t-wave oversensing while the transvenous systems were more likely to deliver inappropriate therapy due to SVTs. S-ICD patients had more non-lead related complications which included pocket erosion, defibrillation testing failure and device failure (9.9 % versus.…”
Section: Implantable Cardioverter-defibrillator Device Selectionmentioning
confidence: 99%
“…Although avoiding a transvenous device is appealing, it should be noted that there may be a comparable risk of non-lead-related complications over a lifetime. 42 As such, larger studies with longer-term follow-up will be necessary to further clarify relative benefits of S-ICD therapy in this patient population. One important consideration for S-ICD use in BrS patients is the potential need to perform vector testing to evaluate the patient's suitability for implantation during drug challenge, when the type 1 ECG pattern is transient.…”
Section: Treatmentmentioning
confidence: 99%